Application of artificial intelligence in a technology startup company - Joska Junior, João; Bertoldi, Werner José; Santos, Ruan Carlos dos; Belli, Rodrigo Fernando (Review of Artificial Intelligence in Education, 2023)
Purpose: This study addresses the application of artificial intelligence in the business context and evaluates how the implementation process is, with the aim of improving the efficiency of the organization, by researching the historical basis of AI, the analysis of AI in the current business context and the socialization between the members of the organization. Results: The company that is the subject of the study is a marketing and technology platform development agency that is going through the process of internalizing the tools in its daily life. Investigating the relationship between the application of AI and team efficiency, as well as the company’s capacity for evolution. Method: The work was based on qualitative research with a sample of 131 people and for a group of 5 interviewees, taking into account their understanding of and experience with the tools. Conclusions: The work highlights artificial intelligence as a structure that contributes to the evolution of individuals and organizations, while at the same time discussing how it will be implemented, its applicability and the behaviour of society in the face of possible changes.